Research Progress and Mechanism Analysis of Different Acupuncture Methods in the Treatment of Cognitive Dysfunction after Stroke - He, Tian; Xie, Ximei (Journal of Contemporary Medical Practice, 2025)
Post-stroke cognitive impairment (PSCI) is one of the common sequelae of stroke patients. At present, a large number of studies have been devoted to discovering and improving the treatment methods of cognitive dysfunction after stroke, among which acupuncture treatment as a traditional Chinese medicine therapy has attracted much attention. Acupuncture can obtain therapeutic effects by stimulating specific acupoints, which can adjust the physiological functions of the body and promote the recovery of patients. This article will review the research progress of different acupuncture methods in the treatment of cognitive dysfunction after stroke, aiming to provide guidance and reference for clinical practice.